The Distortive Effects of Antitrust Fines Based on Revenue - Giancarlo Spagnolo; Vasiliki Bageri; Yannis Katsoulacos (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2012)
In most jurisdictions, antitrust fines are based on affected commerce rather than on collusive profits, and in some others, caps on fines are introduced based on total firm sales rather than on affected commerce. We uncover a number of distortions that these policies generate, propose simple models to characterize their comparative static properties, and quantify them with simulations based on market data. We conclude by discussing the obvious need to depart from these distortive rules-of-thumb that appear to have the potential to substantially reduce social welfare.
Keywords: K21; L40; 330; Antitrust; Deterrence; Fines; Law Enforcement